Mutu kulit chamois dari kulit domba peranakan merino - Bambang Oetojo (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 1992)
The purpose of this research is to compare the quality of chamois leather output from merino descendent to that one from local sheep skin. In the actualization it was used four pieces of merino descendent sheep skin and four pieces of local sheep skin. The skins was processed into chamois leather. Chamois leathers output from this research, either from merino descendent sheep skin or local sheep skin were visually investigated. Statistical analysis points out that there is unsignify difference (P ≤ 0,05) the influence of the species either it is merino descendent sheep skin or local one to the quality of chamois leather. Practical meaning of this research is that merino descendent sheep skin may be tanned into chamois leather having some quality to that one from local sheep skin.